Incremental Housing and the Material Blind Spot in Sub-Saharan Africa - Nikol Hoiderková; Sikama Moses Sekenwa (My University, 2026)
Urbanization in sub-Saharan Africa is largely through auto-construction, and incremental housing serves as the de facto city-making scheme. Urban resilience discourse leans heavily on the location and legality of incremental housing settlements, therefore missing a critical blind spot in materiality (the physical substance of the houses). This paper addresses this blind spot by arguing that the “Standard Trajectory” that favors industrial materials such as concrete is more than just a financial and technical decision. It is a profound bid to be a legitimate urbanite through material citizenship. Through the analysis of Environmental Imaginary (the social prestige of durability) and Structural Market Constraints (the "Cement-Concrete Complex"), we identify a dominant Maladaptation Trap. This trap explains why, in attaining social legibility, homeowners are often exposed to thermally hostile and financially rigid structures. We also demonstrate a dependency created by the cement industry, which marginalizes sustainable alternatives. The paper concludes that genuine urban resilience needs to dismantle this trap by giving sustainable materials more visibility, accessibility, and aspirational desirability, similar to concrete.
Submitted for consideration to the SGAS/SSEA & VAD Conference (Basel, 2026), to the Planetary Health, Urbanization, and Natural Resources Panel. This version has not yet been peer-reviewed.
Keywords: Incremental Housing; Urban Resilience; Sub-Saharan Africa; Materiality; Maladaptation; Concrete; Vernacular Architecture; Climate Change